KEPUASAN PELAKSAAAN COMMUNITY DEVELOPMENT INDONESIA POWER SURALAYA: BAGENDUNG ESENSI - Kendali, Krisloana; Aindrasyam, Benanda D; Masyhadi, Luthfie; Ardiansyah, Ahmad N; Fatmawati, Megalia; Sapto Nugroho, Kandung (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2024)
PLN Indonesia Power Suralaya PGU is an example of a public organizational entity in the form of state representation in corporate form. As a corporation, this company is not only profit-oriented but also thinks about the benefits for society. In carrying out corporate actions, PT PLN Indonesia Suralaya PGU will definitely interact with community activities that have the potential for conflict if not maintained properly. These activities can be in harmony with community activities, but it is also undeniable that they are very likely to cause conflict with the community. The community development work program is structured based on opportunities and challenges, problems that exist in the area where problem empowerment is located. Bagendung Village, Cilegon City, was chosen because there is already a Final Waste Disposal Site (TPSA) in collaboration between the Cilegon City government and PT PLN Indonesia Power Suralaya PGU which is managed as Kampeng Energi because Bagendung TPSA is processed into electrical energy. TPSA Sampah Bagendung manages waste into fuel for the Suralaya Steam Power Plant (PLTU). In conclusion, the majority of the Bagendung Essence Program is able to have an impact on increasing welfare for beneficiaries and provides positive benefits for very capable beneficiaries as much as 90 percent, only 10 percent answered that they are able and none at all answered that they are less capable or unable to provide positive benefits for recipients. benefit.